(untitled) (Ciudades, 2018)
In most European countries, among them France, the regulations of retail activities are achieved in two different fields, which work independently. In the field of town and regional planning, the procedure’s goal is to get a building permission, while a commercial authorization is given to start the retail activity. In other countries, such as Great Britain or Sweden, only a planning permission is requested to locate buildings in which retail activities are run. In principle, the “double path” model can be followed in several ways, with different levels of graduation for the predetermination of the areas or number of retail activities. In France, it seems that the choice of a model where the regulation is managed by a commercial authorization has led the government authorities to adopt more and more a quantitative approach to decide the amount of areas or retail activities to leave. The studies and inquiries, which are requested to justify this approach, often seem to aim at finding a vain “best” balance between the demand of the consumers and the offer of retail activities.